ANALISIS IDENTIFIKASI SEKTORUNGGULAN DANSTRUKTUR EKONOMI DI KABUPATEN KEPULAUAN MERANTI - Res Tarida Feberina; Eliza '; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The leading sector can ascendant to economic structured change. The process of change in the economic structure characterized by, the decline in the share of the primary sector, the increase in the share of the secondary sector and the share of the tertiary sector. The purpose of the analyze is identify of the leading sector and the shift of economic structure change at Regency Kepulauan Meranti period 2008-2012. The analytical tool used is the shift fshare analysis (SS) and the method of location quotient (LQ). The data used are secondary data obtained from the Central Statistics Agency. Observational result that becomes to leading sector at Kepulauan Meranti regency with migas which is agricultural sector, processing industry, electricity, gas and fresh water, commerce, hotel and restaurant. Meanwhile without migas which is agricultural sector and commerce, hotel and restaurant. The economic structure in Kepulauan Meranti regency has shifted from the primary sector to the secondary sector, although the rate of shifts is still relatively small, characterized by the percentage contribution of the primary sector has declined, while the contribution of the secondary sector and the tertiary increased.   Key Words: Leading Sectors, Location Quotion, Shiftshare, Economic Structure